PD-L1 is highly expressed in lung lymphoepithelioma-like carcinoma: A potential rationale for immunotherapy. Issue 3 (June 2015) - Chang, Yih-Leong; Yang, Ching-Yao; Lin, Mong-Wei; Wu, Chen-Tu; Yang, Pan-Chyr
Highlights PD-L1 refers to a target for immunotherapy of NSCLC, but its role in LELC is unclear. LELC is highly associated with EBV infection. Driver mutations are infrequent in LELC. Our data first show that PD-L1 expression is a common feature (75.8%) in LELC. These findings may provide a rationale for immunotherapy in LELC.